Elasto-plastic finite element analysis of isotropic plates with d-notches - Arslan, Nurettin; Turgut, Aydin; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 1996)
Elasto-plastic stress analysis of the U-notched isotropic steel plates (SAE 1060) has been carried out using the finite element method (FEM). Isoparametric rectangular elements with four nodes have been employed and the Lagrange polynomial has been used as interpolation function Mechanical properties and yield strength of the U-notched plates have been obtained experimentally using a tensile testing machine. The spreads of the plastic zones have been illustrated for varies cases. Residual stress and equivalent stresses obtained have been presented in diagrams and compared with some of the relevant studies in the literature. The tensile loads of the isotropic plates with U-notches have been shown to increase due to residual stresses which take place under plane stress conditions. © 1996 American Society of Mechanical Engineers (ASME). All rights reserved.
ASME 1996 International Mechanical Engineering Congress and Exposition, IMECE 1996 -- 17 November 1996 through 22 November 1996 -- Atlanta -- 191356
Keywords: Elastoplasticity; Finite element method; Materials testing apparatus; Stress analysis; Tensile testing; Elasto-plastic finite element analysis; Elasto-plastic stress; Interpolation function; Iso-parametric; Isotropic plates; Isotropic steels; Lagrange's polynomials; Steel plates; Stresses analysis; Tensile testing machines; Residual stresses